Mengembangkan Kreativitas Anak Usia Dini Melalui Strategi 4P (Pribadi, Pendorong, Proses, Produk) - Rahimah, Rahimah (Educreative : Jurnal Pendidikan Kreativitas Anak, 2019)
In connection with the development of student creativity, we need to review fouraspects of creativity, namely personal, driving, process, and product (4P of creativity).This unique person can be expected to arise. From this unique personal expression canbe expected the emergence of new ideas and innovative products. Thereforeeducation should be able to appreciate the personal uniqueness and talents of theirstudents, the teacher should help his students find their talents and appreciate them.Students' creative talent will be realized if there is encouragement and support fromtheir environment, or if there is a strong urge in themselves (internal motivation) toproduce something. To develop creatively, children need to be given the opportunityto actively engage themselves. Educators should be able to stimulate themselves toengage in creative activities, by helping to work out the necessary facilities andinfrastructure. This study aims to develop children's creativity and can be developedoptimally, because it is one indicator of the success of education that is able to carryout one of its tasks, namely creating people who are able to do something new, notonly repeat what the previous generation has done . They are creative people, findingsomething that has never existed or combining something that already exists becomesnew.